PENGARUH MOTIVASI, KOMUNIKASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PENDIDIKAN KOTA SEMARANG (Students' Journal of Economic and Management, 2015)
This study aims to determine how the influence of motivation on employee performance, the effect of communication on the performance of employees, and the influence of labor discipline on employee performance. The population in this study were employees of the Department of Education Semarang city, amounting to 128 people. The sampling technique used is random sampling (random) amount to 56 respondents in the sample data collection method using a questionnaire (questionnaire) by distributing a list of statements to the respondents in order to obtain information. The results of multiple regression test showed that motivation significant positive effect on the performance of employees in Semarang City Department of Education. Communication significant positive effect on the performance of employees in Semarang City Department of Education. Labor discipline proved significant positive effect on the performance of employees in Semarang City Department of Education, as well as motivation, communication and discipline work together proved to have a significant effect on the performance of employees in Semarang City Department of Education. Keywords: Motivation, Communication, Work Discipline and employee performance